Fast Distributed Polynomial Multiplication Algorithm for Lattice-based Cryptographic Decryption In Blockchain Systems - Zhao, Hongjian; Tao, Yunting; Kong, Fanyu; Zhang, Guoyan; Zhang, Hanlin; Yu, Jia (Proceedings of the ... International Symposium on Parallel and Distributed Processing with Applications (Print), 2024)
Lattice-based Post-Quantum Cryptography (PQC) can effectively resist the quantum threat to blockchain's underlying cryptographic algorithms. Blockchain node decryption is one of the most commonly used cryptographic computations in blockchain systems, and polynomial multiplication, a time-consuming operation for decryption, is one of the factors limiting blockchain efficiency. This paper proposes a novel distributed computing algorithm for polynomial multiplication, applicable in blockchain decryption. By splitting polynomials into lower-degree terms and delegating tasks to distributed nodes, our approach reduces computation time. A novel verification strategy based on the Karatsuba algorithm ensures result accuracy. The experimental results demonstrate that our proposed scheme improves the execution efficiency of NTT and INTT operations by approximately 47.8% and 52.4%, and reduces Kyber decryption time by up to 23.5%.